The Fortification with Red Dragon Fruit (Hylocereus polyrhizuz) Peel Extract Evaporated with Mae Method Towards the Physic-Chemistry Quality of Symbiotic Yoghurt (Faculty of Animal Science Universitas Brawijaya, 2023)
This study aims at determining the optimum fortification with red dragon fruit peel extract evaporated with MAE method towards the physicchemistry characteristics of symbiotic yogurt. The research object is symbiotic yogurt made of pasteurized fresh milk, red dragon fruit peel extract evaporated with Microwave Assisted Extraction (MAE) method and evaporated with rotary vacuum evaporator, and yoghurt starter containing lactic acid bacteria: Streptococcus thermophilus and Lactobacillus bulgaricus (1:1). The study employs an experiment with Complete Random Design in four treatments including without fortification with red dragon fruit peel extract (P0) and with fortification with red dragon fruit peel extract at 10% (P1), 20% (P2), and 30% (P3) (v/v) with three replications. The variables to be analyzed include physical quality (pH, viscosity, syneresis), color (L*, a*, b*) and chemical quality (acid total, lipid and protein level). The data were analyzed using Analysis of Variance (ANOVA). If there was a difference, the analysis would be continued using Duncan multiple Range Test. The result indicates that the fortification with red dragon fruit peel extract shows significant differences on the pH level (P<0,05), viscosity (P<0,01), syneresis, color (L*, a*, b*) and chemical quality of symbiotic yoghurt. Fortification with red dragon fruit peel extract reduces the pH level and syneresis while it increases viscosity, total acid and protein level because of the fiber content i. e. pectin which functions as a stabilizer. Moreover, it also decreases the lipid profile and increases the turbidity (L*, b* and a*) values. It is concluded that the optimum fortification of 20% with red dragon fruit peel extract evaporated using MAE method results in symbiotic yoghurt observed from its physic-chemistry quality.